To solve the equation \( x^2 + 4x = 18 \) by completing the square, let's go through the steps.
-
Start with the original equation: \[ x^2 + 4x = 18 \]
-
Move the constant to the other side: \[ x^2 + 4x - 18 = 0 \]
-
To complete the square, take half of the coefficient of \( x \) (which is 4), square it, and add it to both sides. Half of 4 is 2, and squaring it gives \( 2^2 = 4 \).
-
Rewrite the equation as: \[ x^2 + 4x + 4 = 18 + 4 \] This simplifies to: \[ x^2 + 4x + 4 = 22 \]
-
Now, write the left-hand side as a squared term: \[ (x + 2)^2 = 22 \]
-
Take the square root of both sides: \[ x + 2 = \pm \sqrt{22} \]
-
Solve for \( x \): \[ x = -2 \pm \sqrt{22} \]
-
Now calculate \( \sqrt{22} \), which is approximately 4.690 (rounding to the nearest tenth gives 4.7). Thus: \[ x = -2 + 4.7 \quad \text{and} \quad x = -2 - 4.7 \] This gives: \[ x = 2.7 \quad \text{and} \quad x = -6.7 \]
Now, we can fill in the response area based on these calculations:
- x squared plus 4 x plus: 4
- equals 18 plus: 4
- left-parenthesis x plus: 2
- right-parenthesis squared equals: 22
- x plus: 2
- equals plus or minus: 4.7
- x equals: 2.7
- and negative: 6.7
So, the final answers are:
- x squared plus 4 x plus: 4
- equals 18 plus: 4
- left-parenthesis x plus: 2
- right-parenthesis squared equals: 22
- x plus: 2
- equals plus or minus: 4.7
- x equals: 2.7
- and negative: 6.7